Calidad y evaluación en las instituciones técnicas y tecnológicas en Colombia (Papeles, 2011)
This research presents the state of the art synthesis systems evaluation in technical and technological institutions in Colombia, from things like the current regulations on National Higher Education, institutional documents and statistical data from the National Information System SNIES Higher Education, the National Accreditation Council and the Ministry of Education. The study was conducted under a descrptive and purposeful approach. As a result we present the identification of the criteria underlying the selection, retention, promotion and grade of students in technical and technological institutions in the city of Bogota.
Keywords: Evaluation Systems; Technical Institutions; Technological Institutions; Standards; Higher Education